Austen at sea - Jenner, Natalie (St. Martin's Press, 2025)
"Two pairs of siblings, devotees of Jane Austen, find their lives transformed by a visit to England and Sir Francis Austen, her last surviving brother and keeper of a long-suppressed, secret legacy. In Boston, 1865, Charlotte and Henrietta Stevenson, daughters of a Massachusetts Supreme Court Justice, have accomplished as much as women are allowed in those days. Chafing against those restrictions and inspired by the works of Jane Austen, they start a secret correspondence with Sir Francis Austen, her last surviving brother, now in his nineties. He sends them an original letter from his sister and invites them to come visit him in England. In Philadelphia, Nicholas & Haslett Nelson - bachelor brothers, veterans of the recent Civil War, and rare book dealers - are also in correspondence with Sir Francis Austen, who lures them, too, to England, with the promise of a never-before-seen, rare Austen artifact to be evaluated. The Stevenson sisters sneak away without a chaperone to sail to England. On their ship are the Nelson brothers, writer Louisa May Alcott, Sara-Beth Gleason - wealthy daughter of a Pennsylvania state senator with her eye on the Nelsons - and, a would-be last-minute chaperone to the Stevenson sisters, Justice Thomas Nash. It's a voyage and trip that will dramatically change each of their lives in ways that are unforeseen, with the transformative spirit of the love of literature and that of Jane Austen herself"--